PERFORMANCE OF FINGER MILLET VARIETIES UNDER VARIOUS LEVELS OF NITROGEN - Krishnamurthy, K (Annals of Arid Zone, 2016)
Investigations were undertaken in two field trials at the Agricultural College, Dharwar, India on the performances of four finger millet varieties (H-22, Cauvery. Annapurna and Purna) in relation to four levels of Nitrogen (0, 50, 100, 150 nitrogen kg/ha). These treatment combinations were laid out in factorial design with four, replications. The crop was raised under transplanted conditions. It was observed that vadety Purna was not suited for this transition rain fed tractÂ· while Annapurna performed better. Though all the varieties produced higher grain yield at 150 kg nitrogen hectare yet the differences in grain yield between 100-150 kg nitrogen-levels were not significant. Higher grain yield in Annapurna bore some relation to higher tiller number.